Present tense form usage by Arab and Malay users of English - Zulkifli, Siti Khadijah; Lotfie, Maskanah Mohammad (2018)
Issues concerning the acquisition of English as the second language (L2) have been perpetually discussed in reference to the influence of the first language (L1). This research is a comparative study of written simple present time forms of English among the Malay and Arab learners of English. It seeks to find out the temporal similarities and differences between the three languages. It should help in clarifying theoretical understanding between the three languages in the area of temporal references. Data was collated in the form of written output of sixty respondents consisted of advanced users of English as the second language of Malays and Arabs. To facilitate the comparison, the participants were asked to write an English essay of about 400 words within forty-five minutes on a given topic. The research is expected to provide substantial evidence on the acquisition patterns of Malay and Arab users of English concerning English simple present form.